Standar Pengelolaan Pendidikan Dasar - Muthmainnah, Wildatul; Putri, Julia; Adilla, Putri; Ananda, Rizki (Lembaga Yasin AlSys, 2023)
Education is one of the basic needs in human thinking life and one of the basic needs as part of the life and survival of humans in this world who are doing the work of the Creator, namely to worship. A very important part of education is the administrative process. Indonesia is one of the developing countries where the quality of education is still low. This can be seen from the low entry and exit rates of vocational training. Indonesia needs to improve the quality of education, including developing a more advanced education management system. This course uses school research as a research method. Library research collects data from various reading sources of books, newspapers and articles which are the source of this research data. Humans are determined to represent society as never before by using the human resources and other resources that education currently provides. Formation of an education system can be started from the beginning of society and the transmission of cultural values. The concept of education today is inseparable from education, education will meet the educational needs of the past, present and future. Administrative standards are national education standards relating to the planning, implementation and monitoring of educational activities in the education sector, district/city, district or at the national level to achieve efficiency and effectiveness in the delivery of education. As one of the national education standards.